Joint Action: Mental Representations, Shared Information and General Mechanisms for Coordinating with Others - Vesper, Cordula; Abramova, Ekaterina; Bütepage, Judith; Ciardo, Francesca; Crossey, Benjamin; Effenberg, Alfred; Hristova, Dayana; Karlinsky, April; McEllin, Luke; Nijssen, Sari R. R.; Schmitz, Laura; Wahn, Basil (Frontiers in Psychology, 2017)
In joint action, multiple people coordinate their actions to perform a task together. This often requires precise temporal and spatial coordination. How do co-actors achieve this? How do they coordinate their actions toward a shared task goal? Here, we provide an overview of the mental representations involved in joint action, discuss how co-actors share sensorimotor information and what general mechanisms support coordination with others. By deliberately extending the review to aspects such as the cultural context in which a joint action takes place, we pay tribute to the complex and variable nature of this social phenomenon.